ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUK DOMESTIK REGIONAL BRUTO PADA SEKTOR INDUSTRI PENGOLAHAN DI KABUPATEN BEKASI - Tandy Adriansyah, (2021)
The Manufacturing Industry Sector is one of the drivers of regional economic development as seen from the Gross Domestic Regional Product (GDRP) indicator in Bekasi Regency. This study aims to determine the effect of labor, investment, and inflation on the GDRP of the processing industry sector in Bekasi Regency. Determination of the sample using purposive sampling technique with 4 variables from 1980 to 2020 so as to reach a total sample of 40. The data used is secondary data obtained from the Central Statistics Agency and the Investment Coordinating Board. The results of the study partially show that (1) labor has a significant effect on the GRDP of the processing industry sector in Bekasi Regency (2) investment has significant no effect on the GRDP of the manufacturing industry sector in Bekasi Regency (3) inflation has no significant effect on the GRDP of the manufacturing industry sector in Bekasi Regency.